Eufemisme Tuturan Calon Presiden 2024 Masa Pemilu pada Youtube Kompas TV - Adel Oktaviani; Ira Eko Retnosari; Agung Pramujiono (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2024)
Abstract Euphemism is a more subtle expression as a substitute for an expression that is considered harsh which aims to protect the feelings of a particular individual or group. In line with this statement, this research examines the forms and functions of euphemisms in the speeches of the 2024 presidential candidates on Kompas TV YouTube. The aim of this research is to identify euphemisms in terms of form and function in speech. The data source in this research is a video on the Kompas TV YouTube account from July 15 2023 to January 7 2024. The video supporting the data was taken using documentation, listening and note-taking techniques. The video collection procedure begins by searching for news topics related to the speech topics of the 2024 presidential candidates during speeches from competing ideas, declarations, political speeches and even the 2024 presidential candidate debates. Each news topic selected is then transcribed. Data analysis uses data reduction, data presentation and conclusions. The research results concluded that in terms of form, euphemisms were found in the categories of foreign terms, abbreviations, acronyms, periphrases, litotes and metaphors. Then, in terms of function, we found euphemisms that refine speech, educational degrees, and protect uncertain statements. Keywords: euphemism, forms of euphemism, function of euphemism, Kompas TV, YouTube